Pertumbuhan Tanaman Bawang Merah (Allium cepa L.) Menggunakan ZPT Organik - Fernanda, Rizky; Wilujeng, Sukian; Isrianto, Pramita Laksitarahmi (Program Studi Biologi, Fakultas Sains dan Teknologi, UNIPAR JEMBER, 2022)
Many people think that Styrofoam is just a waste and cannot be utilized, as time goes by, with the narrower land, styrofoam media is very helpful for planting media. One of them is the cultivation of shallot plants which contain nutrients and active chemical substances that have benefits for health apart from being a complementary spice. In the growth process, of course, shallots need organic compounds as a physiological process known as ZPT. The natural ingredients used as ZPT are cherry water and sprouts extract.The purpose of this study was to determine the use of styrofoam media for the growth of shallot plants using organic ZPT. This research is an experimental study and the research design used a single factor completely randomized design, with 4 levels, namely 0.75, 100, 150 and 170%. Each treatment with four replicates of auxin ZPT, namely the Bio TECH msg 3 brand with a dose of 10g / ml was used as a comparison. Based on the results of the analysis using the ANOVA test, the results were (? = 0.00) for shoot height growth, (? = 0.00) for the number of shoots, (? = 0.00) for the number of roots and (? = 0.00) for the root length. This proves that giving organic auxin ZPT 170% has a significant effect on the growth of shallot plants. So it is recommended that the community when cultivating plants is recommended to use 170% organic auxin ZPT on Styrofoam media because it saves more land and is cheap.